Modulation of basal ganglia local field potentials by deep brain stimulation in Parkinson's disease and dystonia - Wiest, C (2022)
Subthalamic (STN) deep brain stimulation (DBS) is an effective treatment option in advanced Parkinson’s disease, however, its underlying mechanism remains largely speculative. Continuous DBS may come with side effects such as speech impairment, paraesthesia and mood changes, which necessitates research into adaptive DBS. Adaptive DBS requires feedback signals reflecting pathological activity to guide stimulation. Previous studies have focused on beta oscillations in the STN as a potential biomarker for parkinsonian symptoms and beta power suppression has been suggested as a potential action mechanism of DBS. In this thesis, we sought to investigate mechanisms underlying STN stimulation beyond beta power suppression and studied other potential feedback markers to improve current frameworks of adaptive DBS.